2007
DOI: 10.1007/s12016-007-8013-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus (HBV) and Autoimmune Disease

Abstract: The etiology and pathogenesis of autoimmune diseases have long been an enigmatic subject that have involved genetic and environmental factors. Recent intriguing data has contributed to the mechanisms involved, including the relationship of infectious agents and loss of tolerance. This loss of tolerance is illustrated by the data on the immune response to Hepatitis B virus such as the molecular mimicry between HBV antigens and self proteins, the generation of immune complexes between HBV antigens and antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 93 publications
(226 reference statements)
0
81
0
4
Order By: Relevance
“…In fact, a study showed that very few patients with AIH had specific antibodies against HCV suggesting that most of them had never encountered this virus [93] . Other hepatitis-causing viruses such as hepatitis A and B viruses (HAV, HBV) have been proposed as triggers for AIH [94][95][96][97][98] . The Epstein-Barr virus (EBV), has been associated with AIH in several case reports and in a clinical follow-up of 13 patients [66][67][68][69] .…”
Section: Molecular Mimicrymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a study showed that very few patients with AIH had specific antibodies against HCV suggesting that most of them had never encountered this virus [93] . Other hepatitis-causing viruses such as hepatitis A and B viruses (HAV, HBV) have been proposed as triggers for AIH [94][95][96][97][98] . The Epstein-Barr virus (EBV), has been associated with AIH in several case reports and in a clinical follow-up of 13 patients [66][67][68][69] .…”
Section: Molecular Mimicrymentioning
confidence: 99%
“…Hepatitis A virus Case reports [94][95][96] Hepatitis B virus Case reports [97,98] Hepatitis C virus Specific AIH autoantibodies [87][88][89] Cross-Reactivity at T and B-cell level [90][91][92] Epstein-Barr virus Case reports [66][67][68][69] Human herpes virus 6 Sequence similarities [99] Herpes simplex virus Sequence similarities [102] Cross-reactivity at B-cell level [102] 1030…”
Section: Evidences Referencesmentioning
confidence: 99%
“…The joints, muscle, and skin are the main locations of these clinical manifestations. Autoimmune diseases and LPDs, such as malignant lymphoma and mixed cryoglobulinemia, are also common disorders 9 . Furthermore, asymptomatic disorders of immunologic and LPD markers have been observed in patients with CH-B, as well as in patients with CH-C.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have suggested that HBV infection may result in some autoimmune diseases such as glomerulonephritis and polyarteritis nodosa. 15 As newer, more potent immunomodulatory agents are used for rheumatic diseases, these issues will become increasingly important. Future prospective investigations with larger populations are needed.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%